Knots. - Burde, Gerhard, 1931-; Zieschang, Heiner; Heusener, Michael (De Gruyter studies in mathematics., 2013)
This 3. edition is an introduction to classical knot theory. It contains many figures and some tables of invariants of knots. This comprehensive account is an indispensable reference source for anyone interested in both classical and modern knot theory. Most of the topics considered in the book are developed in detail; only the main properties of fundamental groups and some basic results of combinatorial group theory are assumed to be known.